2017
DOI: 10.4317/jced.53582
|View full text |Cite
|
Sign up to set email alerts
|

The effects of three remineralizing agents on regression of white spot lesions in children: A two-week, single-blind, randomized clinical trial

Abstract: BackgroundThis study investigated the effect of three remineralizing agents on improving white spot lesions (WSLs).Material and MethodsThis clinical trial included children who had at least one WSL on anterior teeth of upper or lower jaws. The participants were randomly assigned to 4 groups by treatment: 1) a cream containing casein phosphopeptide-amorphous calcium phosphate and fluoride (MI Paste Plus); 2) a cream containing hydroxyapatite and fluoride (Remin Pro); 3) a 2% sodium fluoride gel; and 4) usual ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
26
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 29 publications
3
26
0
4
Order By: Relevance
“…Enamel remineralization of different calcium-phosphate and uoride delivery systems were assessed with Vyavhare et al, (27) who compared the remineralization potential of uoride, nano-hydroxyapatite, and CPP-ACP and they stated that tested materials had high remineralization potential of uoride. Also, Ebrahimi et al, (28) agreed with the results of multiple studies who proved signi cant reduction of white spot lesions after the use of products containing CPP-ACP or CPP-ACPF. The results of this study agreed with Damyanova et al, (29) who used Clinpro white varnish and TCP and stated that it is effective lessening demineralization within the subsurface layer and in improving the remineralization of surface and subsurface enamel layer.…”
Section: Discussionsupporting
confidence: 78%
“…Enamel remineralization of different calcium-phosphate and uoride delivery systems were assessed with Vyavhare et al, (27) who compared the remineralization potential of uoride, nano-hydroxyapatite, and CPP-ACP and they stated that tested materials had high remineralization potential of uoride. Also, Ebrahimi et al, (28) agreed with the results of multiple studies who proved signi cant reduction of white spot lesions after the use of products containing CPP-ACP or CPP-ACPF. The results of this study agreed with Damyanova et al, (29) who used Clinpro white varnish and TCP and stated that it is effective lessening demineralization within the subsurface layer and in improving the remineralization of surface and subsurface enamel layer.…”
Section: Discussionsupporting
confidence: 78%
“…In the study of Mohan et al ( 31 ) an increase in Ca/p ratio was observed with the combination of laser irradiation and Remin Pro®. This was attributed to the presence of hydroxyapatite crystals in this topical paste ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Remin Pro® is a water-based cream that contains three components: hydroxyapatite, 1450 ppm of fluoride and xylitol as a sugar substitute with cariostatic properties. It is assumed that the ingredients in this topical agent enhance the potential of remineralization; limit the adhesion of bacterial plaque to enamel and reinforce the tooth against further carious attack ( 30 ). The outcomes of this study are similar to those of Mohan et al ( 31 ) who showed an increase in mineral content when CO2 laser irradiation was done before and after the application of Remin Pro® paste on the enamel surface.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in results may be due to the less use of these products compared to the previous studies. [37][38][39][40] Yet, some studies have found no significant difference between these materials and the saliva group, whether used for prevention or treatment, which seems to be due to short-term use of these materials followed by daily irrigation. 11,21,41 Since the duration of use of the material in this study was increased by five minutes each time, no significant difference was observed compared to the control group.…”
Section: Discussionmentioning
confidence: 99%